Diplomacy in the Perspective of Boundaries - Shrestha, Buddhi Narayan (Journal of Foreign Affairs, 2021)
Diplomacy is an instrument for negotiation to find mutually acceptable solutions to a common challenge in a non-confrontational and polite manner. In this perspective, border diplomacy refers to the diplomatic approaches to demarcate, manage and resolve the border disputes in a peaceful manner. For Nepal, border diplomacy for demarcation and management should be based on the dynamic equilibrium of both the neighbours, China and India. This paper revisits the crux of diplomacy and border diplomacy for the peaceful settlement of disputes in a peaceful way. The research emphasizes on border demarcation diplomacy, focussing on Nepal-India and Nepal-China borders. The study explains about the border dispute between Nepal and India in the region of Lipulek, Limpiyadhura and Kalapani. Further, the paper suggests border management diplomacy for Nepal-China and Nepal-India, focusing on the Kalapani issue, and alerts about the possible circumstances during the negotiations and recommends Nepal’s potential strategies for border management in the future.